Association of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Infection With Maternal Mortality and Neonatal Birth Outcomes in Botswana by Human Immunodeficiency Virus Status. Issue 1 (30th January 2023) - Jackson-Gibson, Maya; Diseko, Modiegi; Caniglia, Ellen C.; Mayondi, Gloria K.; Mabuta, Judith; Luckett, Rebecca; Moyo, Sikhulile; Lawrence, Pamela; Matshaba, Mogomotsi; Mosepele, Mosepele; Mmalane, Mompati; Banga, Jaspreet; et al.
Abstract : Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection was associated with increased maternal mortality, and most adverse birth outcomes were worse among neonates jointly exposed to SARS-CoV-2 and human immunodeficiency virus (HIV) infection. Abstract : OBJECTIVE: To evaluate the combined association of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and human immunodeficiency virus (HIV) infection on adverse birth outcomes in an HIV-endemic region. METHODS: The Tsepamo Study abstracts data from antenatal and obstetric records in government maternity wards across Botswana. We assessed maternal mortality and adverse birth outcomes for all singleton pregnancies from September 2020 to mid-November 2021 at 13 Tsepamo sites among individuals with documented SARS-CoV-2 screening tests and known HIV status. RESULTS: Of 20, 410 individuals who gave birth, 11, 483 (56.3%) were screened for SARS-CoV-2 infection; 4.7% tested positive. People living with HIV were more likely to test positive (144/2, 421, 5.9%) than those without HIV (392/9, 030, 4.3%) ( P =.001). Maternal deaths occurred in 3.7% of those who had a positive SARS-CoV-2 test result compared with 0.1% of those who tested negative (adjusted relative risk [aRR] 31.6, 95% CI 15.4–64.7). Maternal mortality did not differ by HIV status. The offspring of individuals with SARS-CoV-2 infection experienced more overall adverse birth outcomes (34.5% vs 26.6%; aRR 1.2, 95% CI 1.1–1.4), severe adverse birth outcomes (13.6% vs 9.8%; aRR 1.2, 95% CI 1.0–1.5), preterm delivery (21.4% vs 13.4%; aRR 1.4, 95% CI 1.2–1.7), and stillbirth (5.6% vs 2.7%; aRR 1.7 95% CI 1.2–2.5). Neonates exposed to SARS-CoV-2 and HIV infection had the highest prevalence of adverse birth outcomes (43.1% vs 22.6%; aRR 1.7, 95% CI 1.4–2.0). CONCLUSION: Infection with SARS-CoV-2 at the time of delivery was associated with 3.7% maternal mortality and 5.6% stillbirth in Botswana. Most adverse birth outcomes were worse among neonates exposed to both SARS-CoV-2 and HIV infection.